The Evaluation by the Financial Markets of Changes in Bank Loan Loss Reserve Levels - Elliott, John A.; Hanna, J. Douglas; Shaw, Wayne H. (The Accounting Review, 1991)
[In this article, we examine the information content of announcements of increased reserves for loan loss by Citicorp and other banks, and the later write-off announcement made by the Bank of Boston. During 1987, most major U.S. banks, led by Citicorp on 19 May 1987, announced large increases in their loan loss reserves because of problem loans in lesser developed countries (LDC). With substantial flexibility in accounting rules for determining loss exposure, the banks announced varying levels of reserve increases. On 14 December 1987, the Bank of Boston began a second round of activity relating to LDC debt by announcing a $200 million write-off of LDC loans and further increase in loan loss reserves. Financial reporters suggested that these events could be interpreted differently. Because Citicorp was a leading money-center bank, its announcement could be interpreted favorably as a signal of willingness to deal with the LDC debt problem. This interpretation could similarly apply to other banks, especially the more exposed money-center banks. In comparison, the Bank of Boston announcement was portrayed in the press as detrimental to the money-center banks for two reasons. First, unlike a reserve increase, a write-off reduces a bank's capital adequacy ratio. Capital adequacy ratios are used by bank regulators in determining the need for, and the level of, supervisory intervention. Second, the write-off was construed as an effort by regional banks to exploit their relatively limited exposure to LDC loans as a competitive advantage in the domestic banking market. We find evidence consistent with the expectations of the financial press. The strongest stock-price increases associated with both the Citicorp announcement and the subsequent announcements of reserve increases by other banks were found for the banks with the greatest exposure to LDC debt. In contrast, those banks with the greatest exposure to LDC debt and with the largest reserves sustained the largest stock-price decreases at the Bank of Boston write-off announcement. The larger money-center banks sustained, on average, a three-day decline in value of 5 percent around the Bank of Boston announcement date.]